Solving post-prandial reduction in performance by adaptive regurgitation in a freshwater fish - Zhao, Jian; Wen, Yanci; Zhu, Songming; Ye, Jinyun; Zhu, Junjie; Ye, Zhangying; Jordan, Alex (My University, 2020)
Foraging animals must balance benefits of food acquisition with costs induced by a post-prandial reduction in performance. Eating to satiation can lead to a reduction in locomotor and escape performance, which increases risk should a threat subsequently arises, but limiting feeding behaviour may be maladaptive if food intake is unnecessarily reduced in the prediction of threats that do not arise. The efficacy of the trade-off between continued and interrupted feeding therefore relies on information about the future risk, which is imperfect. Here, we find that black carp (Mylopharyngodon piceus) can balance this trade-off using an a posteriori strategy; by eating to satiation but regurgitating already ingested food when a threat arises. While degrees of satiation (DS) equal to or greater than 60% reduce elements of escape performance (turning angle, angular velocity, distance moved, linear velocity), at 40% DS or lower, performance in these tasks approaches levels comparable to that at 0% satiation. After experiencing a chasing event, we find that fish are able to regurgitate already ingested food, thereby changing the amount of food in their gastrointestinal tract to consistent levels that maintain high escape performance. Remarkably, regurgitation results in degrees of satiation between 40 and 60% DS, regardless of whether they had previously fed to 40, 60 or 100% DS. Using this response, fish are able to maximize food intake, but regurgitate extra food to maintain escape performance when they encounter a threat. This novel strategy may be effective for continual grazers and species with imperfect information about the level of threat in their environment.
Keywords: 570